Web-Based Logistics Scheduling System Utilizing Cheapest Insertion Heuristic Algorithm - Chevanton Ernesto Guevara; Raymond Sunardi Oetama; David Tjahjana (Universitas Islam Raden Rahmat, Malang, 2025)
Efficiency in the logistics process is essential to maintain company credibility. Significant improvements in logistics efficiency can be achieved by integrating information systems. However, several companies have not implemented this system. These companies will face logistical challenges, especially in scheduling, which will cause delays in the delivery of goods. Against this challenge, this research aims to build a web-based information system to optimize logistics scheduling. This system aims to provide drivers with a compelling sequence of delivery points by applying the Cheapest Insertion Heuristic algorithm, which is integrated with the Google Maps API. This system will undergo a prototyping phase with a web-based approach using the Laravel framework, supported by PHP and MySQL for database management. This design will follow the Rapid Application Development method. User Acceptance Testing shows an average satisfaction score of 98%, which indicates that users feel significantly helped by the information system, especially in improving the company's delivery scheduling process.